Evaluation of role 2 (R2) medical resources in the Afghanistan combat theater: Initial review of the joint trauma system R2 registry. (November 2016) - Mann-Salinas, Elizabeth A.; Le, Tuan D.; Shackelford, Stacy A.; Bailey, Jeffrey A.; Stockinger, Zsolt T.; Spott, Mary Ann; Wirt, Michael D.; Rickard, Rory; Lane, Ian B.; Hodgetts, Timothy; Cardin, Sylvain; Remick, Kyle N.; et al.
Abstract : BACKGROUND: A Role 2 registry (R2R) was developed in 2008 by the US Joint Trauma System (JTS). The purpose of this project was to undertake a preliminary review of the R2R to understand combat trauma epidemiology and related interventions at these facilities to guide training and optimal use of forward surgical capability in the future. METHODS: A retrospective review of available JTS R2R records; the registry is a convenience sample entered voluntarily by members of the R2 units. Patients were classified according to basic demographics, affiliation, region where treatment was provided, mechanism of injury, type of injury, time and method of transport from point of injury (POI) to R2 facility, interventions at R2, and survival. Analysis included trauma patients aged ≥18 years or older wounded in year 2008 to 2014, and treated in Afghanistan. RESULTS: A total of 15, 404 patients wounded and treated in R2 were included in the R2R from February 2008 to September 2014; 12, 849 patients met inclusion criteria. The predominant patient affiliations included US Forces, 4, 676 (36.4%); Afghan Forces, 4, 549 (35.4%); and Afghan civilians, 2, 178 (17.0%). Overall, battle injuries predominated (9, 792 [76.2%]). Type of injury included penetrating, 7, 665 (59.7%); blunt, 4, 026 (31.3%); and other, 633 (4.9%). Primary mechanism of injury included explosion, 5, 320 (41.4%); gunshot wounds, 3, 082 (24.0%); and crash, 1, 209 (9.4%). Of 12, 849 patients who arrived at R2, 167 (1.3%) were dead; of 12, 682 patients who were alive upon arrival, 342 (2.7%) died at R2. CONCLUSION: This evaluation of the R2R describes the patient profiles of and common injuries treated in a sample of R2 facilities in Afghanistan. Ongoing and detailed analysis of R2R information may provide evidence-based guidance to military planners and medical leaders to best prepare teams and allocate R2 resources in future operations. Given the limitations of the data set, conclusions must be interpreted in context of other available data and analyses, not in isolation. LEVEL OF EVIDENCE: Epidemiologic study, level IV.